THE IMPROVEMENT OF PEDAGOGICAL COMPETENCE OF TEACHERS THROUGH COACHING MODEL APPROACH IN SDN GADING VII SURABAYA - Riyo Darminto (LPPM STAI Muhammadiyah Probolinggo, 2020)
The supervision to be carried out through PTS is a group supervision with collaborative approach. The purpose of this supervision is to improve the competence of lower-grade teachers in making thematic learning plans. Thus, this research is entitled